Production and quality of Mombaça grass forage under different residual heights - Carvalho, Ana Luiza Silva; Martuscello, Janaina Azevedo; Almeida, Otávio Goulart de; Braz, Thiago Gomez dos Santos; Cunha, Daniel de Noronha Figueiredo Vieira da; Jank, Liana (Acta Scientiarum. Animal Sciences, 2017)
This study was conducted to evaluate management strategies in Mombaça grass pastures (Panicum maximum) under intermittent grazing subjected to different residual heights. A randomized-block design with two treatments (two post-grazing residual heights: 30 and 50 cm) and three replications was adopted. Pasture heights pre- and post-grazing, forage mass and accumulation, rest and occupation periods, pasture morphological components, milk yield and quality forage were evaluated. The data were submitted to analysis of variance and the means were compared by the F test at 5% probability. A longer grazing interval was observed in the treatments under the more severe grazing intensity. For forage mass post-grazing, larger production and higher percentage of leaves were found with the 50 cm residue, as well as higher crude protein contents and digestibility of leaves and stems and lower lignin and neutral detergent fiber contents. The residual height of 50 cm is recommended for the management of Mombaça grass pasture, as it provides greater milk yield per animal and a larger number of grazing cycles, ensuring better use of the area.